ANAPLASTIC LYMPHOMA MIMICKING BREAST CARCINOMA - Diniz, Hugo Máximo Oliveira; Sá, Rafael da Silva; Mattos, Tatiana Veri de Arruda; Mattos, Andressa Veri de Arruda; Eburnio, Maycon Luan (Mastology, 2019)
This case describes an uncommon presentation of ALK-negative anaplastic large T-cell lymphoma with breast infiltration, mimicking triple-negative carcinoma. The incidence of ALK-negative anaplastic large T-cell lymphoma usually occurs in adults in their fifth and sixth decade of life and can affect lymph nodes and extranodal sites, including skin, soft tissue, and gastrointestinal tract. The non-Hodgkin’s lymphoma of the breast is uncommon, accounting for 0.04 to 0.05% of all malignant breast tumors. Diagnosis of ALK-negative anaplastic large T-cell lymphoma is challenging both to physicians and pathologists. Based on the complete medical history, clinical and imaging exams and histopathological evaluation of the lesion site biopsy, it is possible to establish an adequate diagnosis. The case describes a woman aged 37 years with palpable nodules in the left breast as well as erythematous lesions on the right leg. The analysis of the breast nodules biopsy shows that they mimic triple-negative carcinoma. However, only with immunohistochemical examination was it possible to verify the expression of the CD30 antigen, and only after a complete systemic evaluation, the diagnosis of ALK-negative anaplastic large T-cell lymphoma was performed. Misdiagnosis can lead to inadequate therapy and result in disease progression or unnecessary damages to the patient.